A strategic roadmap for large-scale green hydrogen demonstration and commercialisation in China: A review and survey analysis. (8th July 2022) - Li, Yanfei; Shi, Xunpeng; Phoumin, Han
Abstract: Hydrogen is gaining increased attention from industries and policymakers in China. However, most of the current demonstration projects in the country have relied on conventional energy sources, including industrial byproduct hydrogen and grey hydrogen produced from fossil fuels. Moreover, strategies and policy frameworks leading to a shift to green or low-carbon hydrogen have neither been explored in-depth nor been identified clearly in the context of China. This study aims at bridging such gaps. Roadmapping techniques enhanced by the Delphi method and SWOT analysis are used to survey hydrogen energy experts from government bodies, industries, and academia to achieve basic agreement on strategically enabling large-scale green hydrogen demonstrations followed by commercialisation in China. The outcome of two rounds of surveys showed that experts' opinions converged on a strategic roadmap with three stages of development. The corresponding policies needed in each stage are evaluated and selected to form a systemic framework. Highlights: Systemic strategies and a policy framework for green hydrogen are called for in China. Roadmapping techniques enhanced by the Delphi method and SWOT analysis are applied. Hydrogen experts from government, industries, and academia in China are surveyed. Experts' opinions converged on a strategic roadmap with three stages of development. Policies needed at each stage are identified and rated to form a systemic framework.